Prevalence And Characteristics Of Gestational Diabetes Mellitus At X Hospital West Jakarta For The Period Of January 2021 - April 2022 - Devi Patricia Kwan; Ricky Susanto (Institute of Computer Science (IOCS), 2022)
Gestational diabetes mellitus that occurs in women during pregnancy is called gestational diabetes mellitus, or commonly abbreviated as DMG. DMG is very dangerous because it has the possibility of complications for pregnant women, such as high blood pressure, large babies born, and also delays in delivery. There is 1 out of 6 births affected by GDM. Meanwhile, according to the 2013 WHO, in Indonesia, around 1.9–3.6% of pregnant women suffer from DMG. The purpose of this study was to determine the prevalence of pregnant women with gestational diabetes mellitus at RS X West Jakarta in the period of January 2021–March 2022. This type of research used descriptive cross-sectional research design. The study was conducted at RS X West Jakarta with a total sample of 2236 mothers who gave birth and a total of 35 of them with gestational diabetes mellitus were selected by non-random Consecutive Sampling that are qualified in inclusion and exclusion criterias to support research related to the prevalence and characteristics of diabetes mellitus. gestational age at RS X West Jakarta. Data was extracted from the medical records of GDM patients who had given birth. There were 6 characteristics of GDM, namely: maternal age at delivery, with an average age of 32 years; gestational age, with an average of 27-30 weeks; the most widely used therapy was insulin (57.1%); the most widely used delivery method was sectio caesarea (80%); the baby's birth weight, with a mean of 3.47 kg; and with the value of the mother's body mass index, the mean value of which is 30.65 (obesity). Suggestions for further research include that research can be carried out with a larger number of subjects to obtain results of prevalence and characteristics that are more accurate.